2021
DOI: 10.3390/toxins13010069
|View full text |Cite
|
Sign up to set email alerts
|

A Wolf in Another Wolf’s Clothing: Post-Genomic Regulation Dictates Venom Profiles of Medically-Important Cryptic Kraits in India

Abstract: The Common Krait (Bungarus caeruleus) shares a distribution range with many other ‘phenotypically-similar’ kraits across the Indian subcontinent. Despite several reports of fatal envenomings by other Bungarus species, commercial Indian antivenoms are only manufactured against B. caeruleus. It is, therefore, imperative to understand the distribution of genetically distinct lineages of kraits, the compositional differences in their venoms, and the consequent impact of venom variation on the (pre)clinical effecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Two studies (Choudhury et al, 2017;Sunagar et al, 2021), compared the venoms of the common krait Bungarus caeruleus and produced different results for venom diversity. The major difference in methodology between the two studies was in protein identification from MS data.…”
Section: Increased Protein Identification By Using a Species-specific...mentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies (Choudhury et al, 2017;Sunagar et al, 2021), compared the venoms of the common krait Bungarus caeruleus and produced different results for venom diversity. The major difference in methodology between the two studies was in protein identification from MS data.…”
Section: Increased Protein Identification By Using a Species-specific...mentioning
confidence: 99%
“…Venom proteomes of snakes have been published with increasing frequency since 2004 (Juárez et al, 2004), with a review published in late 2017 of 132 snake species characterised up to that point (Tasoulis and Isbister, 2017). Individual snake venoms consist of three to approximately 20 different recognised toxin protein families (Sanz et al, 2019;Calvette et al, 2021;Sunagar et al, 2021), made up from a total pool of 57 protein families so far reported in published snake venom proteomes. This total includes a number of regulatory proteins and low abundance protein families of unknown functional or biological significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…provide an instructive example of the effects of such dietary shifts and feeding specialisations on snake venoms. Kraits that chiefly feed on mammals secrete some of the most potent and medically important venoms to humans ( Sunagar et al, 2021 ) whereas those that specialize in feeding on reptiles possess venoms with greatly reduced toxicity to mammals ( Senji Laxme et al, 2019 ). Similar shifts in diet from mammals to arthropods ( Barlow et al, 2009 ; Senji Laxme et al, 2019 ), amphibians ( Hutchinson et al, 2007 ), birds ( Mackessy et al, 2006 ), and eggs of various animals ( Li et al, 2005 ) have significantly influenced the compositions and toxicities of snake venoms and, in some cases, their delivery systems.…”
Section: Snakebite and The “Ecological Stance”mentioning
confidence: 99%
“…Cryptic genetic divergence in clinically important species can be detrimental to snakebite therapy, as antivenoms raised against the venom of one lineage may not be efficient in neutralising toxin variants in genetically distinct snakes. The existence of cryptic evolutionary lineages within a single species, therefore, can have tremendous implications for snakebite treatment, as can the existence of phenotypic crypsis in distinct species with overlapping range-distributions ( Carbajal-Márquez et al, 2020 ; Sunagar et al, 2021 ). More infrequently, evolutionary convergence may result in cryptic lineages which are relatively inconsequential to snakebite therapy, given the convergence of venom composition along with the rest of the phenotype ( Ukuwela et al, 2012 ).…”
Section: Snakebite and The “Ecological Stance”mentioning
confidence: 99%